Excitability, Inhibition, and Neurotransmitter Levels in the Motor Cortex of Symptomatic and Asymptomatic Individuals Following Mild Traumatic Brain Injury - Yasen, Alia L.; Lim, Miranda M.; Weymann, Kristianna B.; Christie, Anita D. (Frontiers in Neurology, 2020)
PURPOSE: The purpose of this study was to determine the level of excitability and inhibition, as well as the concentrations of excitatory and inhibitory neurotransmitters, in the motor cortex of individuals with acute and chronic symptoms from mTBI. METHODS: Fifty-three individuals were assigned to one of four groups: (i) without history of mTBI (Control), (ii) within 72-hours of diagnosis of mTBI (Acute), (iii) with history of mTBI and no remaining symptoms (Chronic Asymptomatic), and (iv) with chronic symptoms from mTBI, lasting at least 3 months post-injury (Chronic Symptomatic). Measures of corticospinal excitability and inhibition were obtained using transcranial magnetic stimulation (TMS). On the same day, measures of glutamate and GABA concentrations were obtained from the primary motor cortex (M1) using proton magnetic resonance spectroscopy. RESULTS: MEP amplitude and area were both significantly lower in the Chronic Symptomatic group compared to the Control and Chronic Asymptomatic groups (p≤0.05). Intracortical inhibition was not significantly different among groups (p=0.14). The concentration of glutamate in M1 was similar between groups (p=0.93) while there was a trend for a lower concentration of GABA in the Chronic Symptomatic group compared to the Acute group (p=0.06). CONCLUSIONS: Individuals with chronic mTBI symptoms appear to have lower corticospinal excitability compared with acutely-injured individuals and asymptomatic controls, but the absence of differences in intracortical inhibition, and concentrations of excitatory and inhibitory neurotransmitters in M1 suggests that neurotransmitter changes in the human brain post-mTBI do not follow the pattern typically seen in the animal literature.